2010
DOI: 10.1007/s10533-010-9511-9
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of whole tree harvesting on soil carbon and nutrient sustainability in the UK

Abstract: The practice of harvesting forest residues is rapidly increasing due to rising demand for renewable energy. However, major concerns have been raised about the sustainability of this practice and its net impact on long term soil ability to support forest productivity, particularly through second and subsequent rotations. In this study, soil chemical properties such as acidity, total N and C, available NO 3 -N and NH 4 -N and exchangeable cations were measured in all horizons in peaty gleys soils under one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 42 publications
3
39
1
Order By: Relevance
“…Probably as a consequence of this, lower growth rates of different conifer species have been observed in experimental stands subjected to WTH than in those subjected to CH (Proe et al, 1996;Egnell and Leijon, 1999;Egnell, 2011). Other effects of WTH include acidification of soil and water and depletion of soil nutrients (Nykvist and Rosén, 1985;Staaf and Olsson, 1991;Olsson et al, 1996b;Johnson and Todd, 1998;Belleau et al, 2006;Thiffault et al, 2006Thiffault et al, , 2011Wall, 2008;Walmsley et al, 2009;Saarsalmi et al, 2010;Vanguelova et al, 2010). Furthermore, leaching may be enhanced by the production of nitrate from decomposing harvest residues (Staaf and Olsson, 1994;Titus et al, 1998;Mahendrappa et al, 2006), which means greater nitrate leaching in CH stands than in WTH stands.…”
Section: Introductionmentioning
confidence: 99%
“…Probably as a consequence of this, lower growth rates of different conifer species have been observed in experimental stands subjected to WTH than in those subjected to CH (Proe et al, 1996;Egnell and Leijon, 1999;Egnell, 2011). Other effects of WTH include acidification of soil and water and depletion of soil nutrients (Nykvist and Rosén, 1985;Staaf and Olsson, 1991;Olsson et al, 1996b;Johnson and Todd, 1998;Belleau et al, 2006;Thiffault et al, 2006Thiffault et al, , 2011Wall, 2008;Walmsley et al, 2009;Saarsalmi et al, 2010;Vanguelova et al, 2010). Furthermore, leaching may be enhanced by the production of nitrate from decomposing harvest residues (Staaf and Olsson, 1994;Titus et al, 1998;Mahendrappa et al, 2006), which means greater nitrate leaching in CH stands than in WTH stands.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of forest soils to act as sinks for atmospheric C, sustain commercial biomass production, and provide other environmental services will likely depend on how well these soils are managed (Fox, 2000;Lal, 2005;Vanguelova et al, 2010). Forest management practices affect soil C and nitrogen (N) storage by changing the quantity or quality of organic matter inputs to the soil, causing physical disturbance of the soil profile, or by modifying the soil environment (temperature and moisture regimes) and nutrient levels (Johnson, 1992;Johnson and Curtis, 2001;Jandl et al, 2007;Nave et al, 2009Nave et al, , 2010Vanguelova et al, 2010). In-line with the increasing demand for renewable energy, interest in the use of planted forests for bioenergy production is growing in New Zealand (Hall et al, 2009) and elsewhere (Vanguelova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Forest management practices affect soil C and nitrogen (N) storage by changing the quantity or quality of organic matter inputs to the soil, causing physical disturbance of the soil profile, or by modifying the soil environment (temperature and moisture regimes) and nutrient levels (Johnson, 1992;Johnson and Curtis, 2001;Jandl et al, 2007;Nave et al, 2009Nave et al, , 2010Vanguelova et al, 2010). In-line with the increasing demand for renewable energy, interest in the use of planted forests for bioenergy production is growing in New Zealand (Hall et al, 2009) and elsewhere (Vanguelova et al, 2010). This demand could lead to the intensification of forest management with associated reductions in the quantities of residues returned to the site following harvesting and the need to apply fertilisers to maintain site productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also identified P as possibly limiting the productivity of temperate hardwood forests [36,37] and multiple sources of evidence indicate that WTH significantly reduces P soil pools [25,38,39]. Estimated P annual budgets in SM-YB forests are between 0.02 [25] and 0.10 kg·ha −1 ·year −1 [35].…”
Section: Implications On Nutrient Pools and Future Forest Productivitymentioning
confidence: 99%